2016
DOI: 10.3892/mmr.2016.5072
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Nogo gene by short hairpin RNA interference promotes functional recovery of spinal cord injury in a rat model

Abstract: The specific myelin component Nogo protein is one of the major inhibitory molecules of spinal cord axonal outgrowth following spinal cord injury. The present study aimed to investigate the effects of silencing Nogo protein with shRNA interference on the promotion of functional recovery in a rat model with spinal cord hemisection. Nogo-A short hairpin RNAs (Nogo shRNAs) were constructed and transfected into rats with spinal cord hemisection by adenovirus-mediated transfection. Reverse transcription‑polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…It is generally accepted that C-terminal region (Nogo-66) of Nogo-A transduces the inhibitory signal into the cell interior of neurons by combining with Nogo-66 receptor (NgR). The research reports that treatment with Nogo shRNAs, which can knockdown Nogo gene expression, improved function recovery of spinal cord injury rats [37]. In the present study, we found that PF treatment suppressed Nogo-A expression in the injured spinal cord.…”
Section: Discussionsupporting
confidence: 69%
“…It is generally accepted that C-terminal region (Nogo-66) of Nogo-A transduces the inhibitory signal into the cell interior of neurons by combining with Nogo-66 receptor (NgR). The research reports that treatment with Nogo shRNAs, which can knockdown Nogo gene expression, improved function recovery of spinal cord injury rats [37]. In the present study, we found that PF treatment suppressed Nogo-A expression in the injured spinal cord.…”
Section: Discussionsupporting
confidence: 69%
“…GAP-43 protein used for the labeling of axonal growth is mainly expressed at the regenerated axonal terminal [18][19][20]. Previously, up-regulation of GAP-43 was associated with the motor function recovery in both brain and spinal cord injury animal models [21][22][23]. In our study, the motor function recovery can be observed in the model group.…”
Section: Discussionsupporting
confidence: 57%
“…In primary retinal ganglion cells, Nogo-A RNA inhibition or a peptide antagonist of the Nogo-66 functional domain promoted axonal outgrowth as assessed using GAP-43 immunofluorescence (Huo et al, 2013 ) suggesting a close relationship between GAP-43 and neurite extension induced by inhibition of Nogo-A function. In rats with spinal cord hemisection, adenovirus-mediated transfection of Nogo-A short hairpin RNAs were found to reduce the expression of the Nogo-A gene and upregulate GAP-43 expression with an associated functional recovery of the injured nerves (Liu et al, 2016 ). Therefore, impeding Nogo gene expression may be an important step leading to the upregulation of GAP-43 in the promotion of spinal cord axonal outgrowth.…”
Section: Gap-43 As a Mediator Of Axonal Outgrowthmentioning
confidence: 99%